CYBERSTALKING: PROBLEMS OF LEGAL PROTECTION - Філінович, Валерія Вікторівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to investigate the features and essence of cyberstalking as a crime in the cyber environment, to point out the legal possibilities of protecting victims of such a crime. Research methods: the research was carried out using generally recognized methods of scientific knowledge, such as: analytical, comparative legal, systemic and structural and others. Results: the concept, essence, characteristics of cyberstalking and related categories were investigated, the problems of protecting Internet users in connection with this crime were indicated, recommendations were given to overcome the problem under consideration. Discussion: the discussion in the article touches upon the aspects of finding ways to solve the problem of cyberstalking, the need to improve and supplement the current domestic legislation, its harmonization with international standards. Today, many crimes, both against the state as a whole, and against individual groups and even specific individuals, are committed online using computers and other devices (also known as «gadgets»). Fraud and forgery, identity substitution, personal data leakage, hacking, spamming, harassment - these are just a few of the cyber problems that many of us face on a daily basis. The so-called cyberstalkers, whose activities often lead to dire consequences, have become especially active in recent years. We can say that the actions called cyberstalking include intimidation, harassment, false accusations, defamation, victim tracking and similar acts committed using gadgets connected to the World Wide Web. Many residents of the post-Soviet expanses are sure that cyber-harassment is not so dangerous, because most often it concerns offensive statements and similar «conversational» actions, rather than real, «physical» actions. But this is a huge misconception, because online harassment quite often turns into harassment in real «offline» life. And in most cases women become victims of such stalking. It is very important to know how this issue is settled in Ukraine, what legal norms can help each of us protect ourselves if cyberstalking affects us or our loved ones.